Ontogenetic changes in the external anatomy of the parasitic castrator crab Calyptraeotheres garthi: Implications for the timing of host colonization and sexual behaviour - Ocampo, Emiliano Hernan (2016)
Pea-crabs are symbiotic crustaceans that live in association with a diverse array of macro-invertebrate hosts. Some pea-crabs exhibit an unusual and incompletely known post-larval cycle characterized by the alternation of free-life and symbiotic forms. We analyzed post-larval morphology, the allometry of various body parts, and sexual dimorphism in Calyptraeotheres garthi, an endosymbiotic pea-crab infesting the brooding chamber of limpets in the southwestern Atlantic. In C. garthi, the smallest invasive crab moults into a male or female prehard stage, which is immediately followed by a hard stage. Then, hard-stage females, but not hard-stage males, pass through four post-hard stages before attaining a fifth terminal stage. The invasive and hard stages exhibit morphological traits (plumose natatory setae on the legs, compressed body shape, and moderate or strong carapace hardness) that likely permit them to swim efficiency while outside of hosts and entering and/or leaving host individuals. In contrast, pre- and post-hard crabs are well endowed for an endosymbiotic lifestyle featuring a soft and rounded carapace, and slender appendages. The allometry of selected traits suggests that males attain sexual maturity during the hard stage and likely roam among host individuals in search of mating opportunities. It remains unclear at which moment females become sexually active and whether hard females abandon host individuals in search of sexual partners.